Preventive Conservation of Vernacular Adobe Architecture at Seismic Risk: The Case Study of a World Heritage Historical City - Neda Haji Sadeghi; Hamed Azizi-Bondarabadi; Mariana Correia (Buildings)
Heritage is strengthened through proactive actions, known as preventive conservation, that are considered before earthquakes, rather than reactive actions addressed when the emergency situation occurs. Considering that there are several regions around the world with very active seismicity, conservation interventions should guarantee human safety and the improvement of the inhabitant’s living conditions while keeping alive the earthen fabric and adobe buildings, thus preserving the lives of the residents but also preserving cultural heritage in the face of earthquakes. The main aim of this paper is to define a comprehensive conservation procedure addressing the preventive conservation of vernacular adobe vaulted houses in Yazd, an Iranian World Heritage property, since 2017. The fundamental phases of this procedure, which this paper’s structure is based on, include introducing the case study and addressing the conservation objectives, the assessment of significance and value, the seismic criteria, the conservation strategies, seismic safety assessment, and decision-making on interventions. The comprehensive preventive conservation procedure presented in this paper was determined by relevant conservation criteria, which contributed to an adequate seismic-retrofitted intervention design. This conservation approach requires evaluation of the seismic performance and the buildings’ safety, through which the decision regarding intervention could be made. Accordingly, this research also dealt with the seismic safety assessment of an adobe building through numerical research work performed using the software HiStrA Ver.2022.1.6. Based on the numerical results, decisions on the need and on the extent of intervention techniques were addressed. In addition, a comparative study was performed on different seismic strengthening techniques available in the literature to define fundamental conservation criteria. In this way, there are more chances for human lives to be preserved if an earthquake occurs.